2008
DOI: 10.1016/j.jtcvs.2007.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Dual immunosuppression enhances vasomotor injury: Interactive effect between endothelin-1 and nitric oxide bioavailability

Abstract: Cyclosporine A and hydrocortisone induce vasomotor dysfunction with a synergistic impairment observed after concomitant exposure. Our findings suggest that the resultant vasomotor dysfunction is the result of alterations in both nitric oxide and endothelin-1 regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…[1][2][3][4] Our group has shown that CsA treatment yields vasomotor dysfunction characterized by impairment in vasorelaxation and increased sensitivity to vasospasm as a result of changes in NO/ET regulation. [5][6][7] Although tacrolimus (Tac) has yet to demonstrate a major difference in rescuing the allograft from refractory rejection or preventing AV, the vascular effects appear more promising. Overall, the literature supports Tac as having a more favorable vascular profile, particularly with regard to two important cardiovascular risk factors: hypertension and dyslipidemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Our group has shown that CsA treatment yields vasomotor dysfunction characterized by impairment in vasorelaxation and increased sensitivity to vasospasm as a result of changes in NO/ET regulation. [5][6][7] Although tacrolimus (Tac) has yet to demonstrate a major difference in rescuing the allograft from refractory rejection or preventing AV, the vascular effects appear more promising. Overall, the literature supports Tac as having a more favorable vascular profile, particularly with regard to two important cardiovascular risk factors: hypertension and dyslipidemia.…”
mentioning
confidence: 99%
“…Although not a transplant model, this was chosen deliberately to evaluate the vascular effects directly related to immunosuppressant exposure, without the confounding factors associated with transplantation such as ischemia/reperfusion injury and host immune response. [5][6][7] Methods Animal care conformed strictly to the Canadian Council on Animal Care's Guide for the Care and Use of Experimental Animals. 8 Male Lewis rats (250 to 350 g, n ϭ 8 per group) were administered the drug of interest (saline control or Tac at 0.5, 1.5 or 3 mg/kg/ day) via intraperitoneal injection for a period of 14 days prior to assessment of vasomotor function.…”
mentioning
confidence: 99%
“…GC treatment in animals leads to impaired endothelial function [24, 25]. As regards the mechanisms involved (Fig.…”
Section: Direct Effects Of Gcs On Endothelial Cells and Functionmentioning
confidence: 99%
“…As regards the mechanisms involved (Fig. 1), decreased vascular availability in NO, the major mediator of endothelial function produced by the vascular endothelial NO synthase (eNOS), has been demonstrated [25], which is secondary to decreased eNOS activity [26], eNOS expression [25], eNOS gene transcription [24], increased degradation of eNOS mRNA [27], decreased eNOS protein stability [24], inhibition of calcium mobilization in endothelial cells [26] or reduction of tetrahydrobiopterin levels, a cofactor required for eNOS enzyme activity [28]. Besides decreasing eNOS activity/expression, GCs have beem found to reduce vascular NO bioavailability by increasing reactive oxygen species (ROS) production.…”
Section: Direct Effects Of Gcs On Endothelial Cells and Functionmentioning
confidence: 99%
See 1 more Smart Citation